Degraded Reality: Using VR/AR to simulate visual impairments - Jones, Pete R.; Ometto, Giovanni (2018 IEEE Workshop on Augmented and Virtual Realities for Good (VAR4Good), 2018)
The effects of eye disease cannot be depicted accurately using traditional media. Consequently, public understanding of eye disease is often poor. We present a VR/AR system for simulating common visual impairments, including disability glare, spatial distortions (Metamorphopsia), the selective blurring and filling-in of information across the visual field, and color vision deficits. Unlike most existing simulators, the simulations are informed by patients' self-reported symptoms, can be quantitatively manipulated to provide custom disease profiles, and support gaze-contingent presentation (i.e., when using a VR/AR headset that contains eye-tracking technology, such as the Fove0). Such a simulator could be used as a teaching/empathy aid, or as a tool for evaluating the accessibility of new products and environments.